2022
DOI: 10.1051/parasite/2022005
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of the morphology ofProfilicollis altmani(Acanthocephala, Polymorphidae) from crustaceans and shore birds in Peru, with special notes on hook elemental analysis (EDXA), SEM imaging, histopathology, and molecular profile

Abstract: The morphology of cystacanths and adults of Profilicollis altmani (Perry, 1942) Van Cleave, 1947 (Polymorphidae) were studied from the Pacific mole crab Emerita analoga (Stimpson) (Crustacea, Hippidae) and Belcher’s gull Larus belcheri (Vigors) (Aves, Laridae), respectively, in Peru. Comparative morphometrics with accounts of other populations of P. altmani from elsewhere off the Pacific and Atlantic coasts of North and South America revealed marked intraspecific population variations. We report scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 59 publications
(175 reference statements)
1
11
0
Order By: Relevance
“…is highly divergent from other species of Profilicollis included in the analysis (COI = 14% and 18S = 21% from P. botulus ). These results are similar to those for the genus Profilicollis previously reported [ 9 , 18 , 54 , 56 ], showing the influence of environmental variables on a specific host-parasite relationships, as well as that mobility of hosts is determinant in the strict parasite-intermediate host links [ 25 , 41 , 54 , 56 ]. Regarding host habitat, environmental conditions may limit acanthocephalan species to particular crab hosts that are exposed to different habitats [ 41 , 56 , 67 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…is highly divergent from other species of Profilicollis included in the analysis (COI = 14% and 18S = 21% from P. botulus ). These results are similar to those for the genus Profilicollis previously reported [ 9 , 18 , 54 , 56 ], showing the influence of environmental variables on a specific host-parasite relationships, as well as that mobility of hosts is determinant in the strict parasite-intermediate host links [ 25 , 41 , 54 , 56 ]. Regarding host habitat, environmental conditions may limit acanthocephalan species to particular crab hosts that are exposed to different habitats [ 41 , 56 , 67 ].…”
Section: Discussionsupporting
confidence: 91%
“…in India, had characteristically very low levels of phosphorus, sulfur, and calcium in anterior, middle, and posterior hooks alike [ 10 ]. A detailed discussion of the biological significance of EDXA as a diagnostic tool is exemplified by the observation that populations of an acanthocephalan species will consistently have similar EDX analysis irrespective of host species or geography, even though comparative morphometrics of different populations of the same species usually vary with host species and geography, as presented in Amin et al [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this species appears as sister species to Andracantha sigma, with a relatively low genetic divergence (10%). In the family Polymorphidae, low genetic diversity has been estimated within species of the genera Andracantha, Corynosoma, Pro licollis, and Tenuisoma [7,18,19,20,21,22]. The same is valid for members of Archiacanthocephala class [23,24].…”
Section: Discussionmentioning
confidence: 92%
“…Most studies have suggested that the classification of the Phylum Acanthocephala based only on morphological characters shows instability due to the conservative and simple morphology of the group (García-Varela & Pérez-Ponce de León 2008;Presswell et al 2018;Amin et al 2019Amin et al , 2022Presswell et al 2020). Therefore, we are assuming that the combination of molecular and morphological tools is a proper approach to resolving taxonomic ambiguities.…”
Section: Discussionmentioning
confidence: 99%